Errors of average ship velocity determination in rolling conditions - Baras, S. T. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The influence of ship rolling on the error determination of horizontal components of ship velocity, established at certain average interval has been analyzed, analytical dependencies showing interrelation between the error of average velocity, basic parameters of Dopler’s log and conditions of its operation - depth, rolling parameters, velocity of sound have been determined